Impact of malnutrition and vitamin deficiency in geriatric patients undergoing orthopedic surgery - Meyer, Matthias; Leiss, Franziska; Greimel, Felix; Renkawitz, Tobias; Grifka, Joachim; Maderbacher , Günther; Weber, Markus (Acta Orthopaedica, 2021)
Background and purpose — There is growing evidence that hypoproteinemia is an important risk factor for adverse events after surgery. Less is known about the impact of vitamin deficiency on postoperative outcome. Therefore we evaluated the prevalence and impact of malnutrition and vitamin deficiency in geriatric patients undergoing elective orthopedic surgery. Patients and methods — In a retrospective analysis of 599 geriatric patients who had undergone elective orthopedic surgery in 2018 and 2019, hypoproteinemia, and deficiency of vitamin D, vitamin B12, and folate were assessed. Reoperation rates, readmission rates, complication rates, and transfusion rates were compared between malnourished patients and patients with normal parameters. Multivariable logistic regression models were used to assess the relationship between malnutrition and postoperative adverse events, controlling for confounding factors such as age, sex, diabetes mellitus, and frailty. Results — Patients with malnutrition showed a higher rate of reoperation (13% vs. 5.5%; p = 0.01) and exhibited more wound-healing disorders (7.4% vs. 1.3%, p = 0.001) as well as Clavien–Dindo IV° complications (7.4% vs. 2.4%; p = 0.03). Deficiency of vitamin D led to a higher rate of falls (8.4% vs. 2.9%, p = 0.006). Deficiency of vitamin B12 and folate did not affect postoperative adverse events. Although correlated to frailty (p = 0.004), multivariable regression analysis identified malnutrition as independent risk factor for reoperation (OR 2.6, 95% CI 1.1–6.2) and wound healing disorders (OR 7.1, CI 1.9–26). Interpretation — Malnutrition is common among geriatric patients undergoing elective orthopedic surgery and represents an independent risk factor for postoperative adverse events.